Creating a soil data base in a reconnaissance soil fertility study of an encroached forest reserve in Northern Nigeria for a reforestation programme - F. O. Adekayode; D. T. Akomolafe (African Journal of Environmental Economics and Management, 2019)
The reconnaissance soil fertility study of 10,000 ha partly encroached forest reserve located between latitude 11°47’N and 11°56’N and longitude 4°22’E and 4°32’E in Northern Nigeria was conducted in 2009 to generate a soil fertility data base of the reserve. The tracking of the forest reserve boundary was done using a Garmin 72 model global positioning system (GPS) receiver. The geographic coordinates were input into the computer to generate a digital map of the forest reserve. The entire forest reserve was divided into grids to guide in the location for soil sampling using the GPS/Geographic Information System (GIS) geospatial technique. Soil auger studies were made at 250 locations to site 60 sampling pits to collect soil samples for laboratory analysis of soil properties. Forest soils were classified into three groups using soil depth as a limiting parameter in the soil fertility assessment. The soils were sandy clay loam and the pH indicated a moderate to strong acid status with low content of organic matter, percentage nitrogen, available phosphorus, potassium, calcium and magnesium. A reforestation programme with the planting of acacia for soil rehabilitation was recommended for the reserve as the tree stands would serve to protect the land against erosive activity of wind and also serve in enriching the soil with nitrogen.